Answer:
(☞゚ヮ゚)☞
Step-by-step explanation:
Hey there! :D
So, we know that there are 3 z's and 3 6's.
3*z= 3z
6*3= 18
3(z+6) <== equivalent expression
3z+18 <== equivalent expression
z is by itself. It shouldn't combine. It should stay the same. 6 as a unit is separate from z.
Choices "B" and "E" are correct.
I hope this helps!
~kaikers
Answer: 36 customers
Step-by-step explanation:
I'm pretty sure because you have to multiply 40 x 6 which is 240 and 6 x 6 which is 36 to get your answer.
Answer: $7.90
Step-by-step explanation:
When we see how much she spent on the total cost of renting skates, getting in, and getting hot chocolate, we can see that she is going to subtract all of that from the total cost.
$15.00 - 2.25 = 12.75
12.75 - 2.15 = 10.60
10.60 - 1.35 = 9.25
9.25 - 1.35 = 7.90 remaining
We know that she payed 2.25 to get in, 2.15 for skate rental, and 1.35 for each hot chocolate she purchased which in this case is 2. We need to subtract all of this from 15 and get the final answer
Answer:
x=-11/6, y=7/6. (-11/6, 7/6).
Step-by-step explanation:
-2x+2y=6
4x+2y=-5
-----------------
2(-2x+2y)=2(6)
4x+2y=-5
----------------------
-4x+4y=12
4x+2y=-5
----------------
6y=7
y=7/6
4x+2(7/6)=-5
4x+14/6=-5
4x=-5-14/6
4x=-30/6-14/6
4x=-44/6
x=(-44/6)/4
x=(-44/6)(1/4)
x=-44/24
simplify
x=-11/6